1989
DOI: 10.1099/00221287-135-1-79
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc Deficiency on the Appearance of Two Immunodominant Protein Antigens (32 kDa and 65 kDa) in Culture Filtrates of Mycobacteria

Abstract: After growth of six strains of mycobacteria on Sauton medium in the absence of added Zn2+, cell yields were lowered, to between 22% and 67% of the yields obtained when Zn2+ (5 microM) was added. Two immunodominant proteins, named P64 and P32 (antigens of 62-65 kDa and 29-33 kDa, respectively) were abundant in culture filtrates after growth of mycobacteria. P64 was present at elevated concentrations (showing a 9- to 16-fold increase as a percentage of the total protein released) after Zn2+-deficient growth of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

1991
1991
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 16 publications
(14 reference statements)
1
24
1
Order By: Relevance
“…The differential expression of the Mtb 65 kDa protein, as detected by HB28 mAb, may be related to the different nutritional environments or to the different levels of metabolic products generated during culture. De Bruyn et al reported that Sauton's medium deficient in zinc enhanced the appearance of two immunodominant protein antigens, 32 kDa and 65 kDa, in culture filtrates of several mycobacterial species (2). However in the present study, where zinc levels were not controlled, only Mtb demonstrated enhanced expression of the 65 kDa protein, not M. bovis BCG or other related mycobacterial species.…”
contrasting
confidence: 78%
“…The differential expression of the Mtb 65 kDa protein, as detected by HB28 mAb, may be related to the different nutritional environments or to the different levels of metabolic products generated during culture. De Bruyn et al reported that Sauton's medium deficient in zinc enhanced the appearance of two immunodominant protein antigens, 32 kDa and 65 kDa, in culture filtrates of several mycobacterial species (2). However in the present study, where zinc levels were not controlled, only Mtb demonstrated enhanced expression of the 65 kDa protein, not M. bovis BCG or other related mycobacterial species.…”
contrasting
confidence: 78%
“…An increase in IgG antibody levels directed against antituberculin, anti-hsp65 or anti-P64 responses was observed in the same subgroup of patients. This was expected, since P64 fragments are present in large amounts in tuberculin [30].…”
Section: Discussionmentioning
confidence: 74%
“…These proteins are associated with the bacterial surface (22) and are major secretory products in Mycobacterium tuberculosis and M. bovis BCG culture fluids (1,6,12). In addition, the 30-kDa protein of this complex, referred to as antigen 85B, has been found to be among the most abundant proteins produced intracellularly in human mononuclear phagocytes (18) and has been demonstrated to be immunoprotective in a guinea pig model of pulmonary tuberculosis (15).…”
Section: Resultsmentioning
confidence: 99%